Long-Term Administration of Triterpenoids From Ganoderma lucidum Mitigates Age-Associated Brain Physiological Decline via Regulating Sphingolipid Metabolism and Enhancing Autophagy in Mice - Zeng, Miao; Qi, Longkai; Guo, Yinrui; Zhu, Xiangxiang; Tang, Xiaocui; Yong, Tianqiao; Xie, Yizhen; Wu, Qingping; Zhang, Mei; Chen, Diling (Frontiers in Aging Neuroscience, 2021)
With the advent of the aging society, how to grow old healthily has become an important issue for the whole of society. Effective intervention strategies for healthy aging are most desired, due to the complexity and diversity of genetic information, it is a pressing concern to find a single drug or treatment to improve longevity. In this study, long-term administration of triterpenoids of Ganoderma lucidum (TGL) can mitigate brain physiological decline in normal aging mice. In addition, the age-associated pathological features, including cataract formation, hair loss, and skin relaxation, brown adipose tissue accumulation, the β-galactosidase staining degree of kidney, the iron death of spleen, and liver functions exhibit improvement. We used the APP/PS1 mice and 3 × Tg-AD mice model of Alzheimer’s Disease (AD) to further verify the improvement of brain function by TGL and found that Ganoderic acid A might be the effective constituent of TGL for anti-aging of the brain in the 3 × Tg-AD mice. A potential mechanism of action may involve the regulation of sphingolipid metabolism, prolonging of telomere length, and enhance autophagy, which allows for the removal of pathological metabolites.